Algorithms as Scores: Coding Live Music. (Leonardo Music Journal, 2011)
The author discusses live coding as a new path in the evolution of the musical score. Live-coding practice accentuates the score, and whilst it is the perfect vehicle for the performance of algorithmic music it also transforms the compositional process itself into a live event. As a continuation of 20th-century artistic developments of the musical score, live-coding systems often embrace graphical elements and language syntaxes foreign to standard programming languages. The author presents live coding as a highly technologized artistic practice, shedding light on how non-linearity, play and generativity will become prominent in future creative media productions.